Evidence on Individual Preferences for Longevity Risk - Gaëtan Delprat; Marie-Louise Leroux; Pierre-Carl Michaud (Center for Economic Studies and ifo Institute (CESifo), 2013)
The standard model of intertemporal choice assumes risk neutrality toward the length of life: due to additivity, agents are not sensitive to a mean preserving spread in the length of life. Using a survey fielded in the RAND American Life Panel (ALP), this paper provides empirical evidence on possible deviation from risk neutrality with respect to longevity in the U.S. population. The questions we ask allow to find the distribution as well as to quantify the degree of risk aversion with respect to the length of life in the population. We find evidence that roughly 75% of respondents were not neutral with respect to longevity risk. Higher income households are more likely to be risk averse. We do not find evidence that the degree of risk aversion varies with age or education.
Keywords: D12; D91; I10; J26; 330; intertemporal choice; risk aversion toward the length of life; stated-preference